Critical issues in global sport management - Schulenkorf, Nico; Frawley, Stephen 1969- (Routledge, Taylor & Francis Group, 2017)
The social, cultural and economic significance of sport has never been more evident than it is today. Adopting a critical management perspective, this book examines the most important themes and challenges in global sport management. From match-fixing, doping, bribery and corruption to corporate social responsibility, governance, and new media, it helps students, researchers and practitioners to understand the changing face of the global sport industry. Written by leading international sport management experts, Critical Issues in Global Sport Management includes twenty chapters and real-life case studies from around the world. It examines contemporary governance and management issues as well as the ethical challenges faced by the global sport industry, including questions of integrity and accountability in recent drug scandals that have been widely reported and debated. This book deals with such questions and many more, highlighting the fact that the global sport system is in urgent need of new and innovative solutions to these ongoing problems.